2011
DOI: 10.1007/s10681-011-0494-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MdMYB1 sequences and expression of anthocyanin biosynthetic and regulatory genes between Malus domestica Borkh. cultivar ‘Ralls’ and its blushed sport

Abstract: A mutant tree with blushed coloring pattern in fruit skin was found and identified as a bud sport of Malus domestica Borkh. cultivar 'Ralls'. This study was aimed at elucidating the genetic basis of this pattern by a comparison of 'Ralls' (striped red) with this bud sport. These two varieties were grown either under normal sunlight (control group) or the fruits were bagged during development (bagged group) and the bags were removed 1 month before harvesting. Anthocyanin content increased during fruit ripening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Other examples include the bleaching of gentian flowers due to mutations in GtMYB3 ( Nakatsuka et al, 2008 ) and the positive regulation of anthocyanin biosynthesis and its effects on organ and tissue-specific anthocyanin accumulation in lily via LhMYB6 and LhMYB12 ( Yamagishi et al, 2010 ). Further studies discovered that sequence variations and methylation levels in MYB transcription factor genes also affected anthocyanin accumulation, but this observation was only reported in studies with fruit trees ( Espley et al, 2009 ; Xu et al, 2012 ) and maize ( Das and Messing, 1994 ; Cocciolone et al, 2001 ; Robbins et al, 2009 ).…”
Section: Anthocyanin Biosynthetic Pathway and Key Genesmentioning
confidence: 99%
“…Other examples include the bleaching of gentian flowers due to mutations in GtMYB3 ( Nakatsuka et al, 2008 ) and the positive regulation of anthocyanin biosynthesis and its effects on organ and tissue-specific anthocyanin accumulation in lily via LhMYB6 and LhMYB12 ( Yamagishi et al, 2010 ). Further studies discovered that sequence variations and methylation levels in MYB transcription factor genes also affected anthocyanin accumulation, but this observation was only reported in studies with fruit trees ( Espley et al, 2009 ; Xu et al, 2012 ) and maize ( Das and Messing, 1994 ; Cocciolone et al, 2001 ; Robbins et al, 2009 ).…”
Section: Anthocyanin Biosynthetic Pathway and Key Genesmentioning
confidence: 99%
“…The increased anthocyanin synthesis in the red bud of “Ralls” was due to higher enzyme activities of CHI and DFR 103 . Additional research on the red bud of “Ralls” showed that the structural genes in anthocyanin biosynthesis were upregulated because of the increased expression of MdMYB1 , and the low methylation level of the MdMYB1 promoter was associated with its increased expression 104 . El-Sharkawy et al suggested that differential methylation levels in the MR3 and MR7 promoter regions of MdMYB10 were the epigenetic factors causing the color mutation 105 .…”
Section: Breeding Of Red-skinned and Red-fleshed Applesmentioning
confidence: 99%
“…Anthocyanin biosynthesis is usually regulated by various TFs, especially the MBW complex [ 29 ]. Previously, MYB was found to be a crucial regulator of anthocyanin accumulation and fruit pigmentation in apples [ 30 , 31 ]. In the present study, 28 R2R3-MYB TFs were identified in skin samples of bagged “Granny Smith” apples following 5-aza-dC treatment, seven of which were significantly upregulated in transcription in the T2 group, corresponding to structural genes related to anthocyanin biosynthesis ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of anthocyanin accumulation has been linked to changes in DNA methylation or demethylation in the promoter of the master anthocyanin regulator MYB [ 15 , 16 , 31 ]. Compared with “Honeycrisp” and “Royal Gala” [ 16 ], differences in methylation levels between control and 5-aza-dC-treated fruits were more obvious in “Granny Smith” [ 17 ], which reflects the striking contrast in pigmentation between the two fruits (i.e., an almost complete loss of anthocyanins in control fruits vs. red pigmentation in 5-aza-dC-treated fruits).…”
Section: Discussionmentioning
confidence: 99%